Composite film layer, composite current collector, preparation method, electrode structure, secondary battery and electric device

By using a composite film layer of a non-polar material and a composite film layer of a surface fabric layer of a polar material in the composite fluid collecting copper foil, the problems of easy corrosion of the intermediate layer material and poor adhesion of the metal layer in the prior art are solved, the mechanical strength and adhesion are improved, and the service life of the lithium battery is extended.

CN119674097APending Publication Date: 2025-03-21JIANGSU ENPACK COMPOSITE CURRENT COLLECTORS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411962527.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

After the existing composite liquid-collection copper foil is used in lithium batteries, the intermediate layer material is easily corroded, resulting in collapse of the material structure, degradation of the lithium battery performance, and poor adhesion of the metal layer and low mechanical strength.

Method used

A composite film layer including an intermediate fabric layer and a surface fabric layer is adopted. The intermediate fabric layer is made of non-polar materials. The surface fabric layer is made of polar materials or a combination of polar and non-polar materials. It is prepared by braiding methods such as warp and weft cross weft to increase the micro-melting intermediate connection layer to improve bonding strength.

Benefits of technology

The bonding strength between polymer materials and metal layers is improved, the mechanical strength and adhesion of the composite fluid-collection copper foil is enhanced, the service life of lithium batteries is extended and the performance is stabilized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674097A_ABST
    Figure CN119674097A_ABST
Patent Text Reader

Abstract

The invention discloses a composite film layer, a composite current collector, a preparation method, an electrode structure, a secondary battery and an electric device. The composite film layer comprises a middle fabric layer and a surface fabric layer connected to at least one surface of the middle fabric layer, the middle fabric layer is made of a non-polar material, and the surface fabric layer is made of a polar material or a combination of the polar material and the non-polar material. According to the composite film layer, the bonding strength between the high polymer material and the metal layer can be improved, and the mechanical strength of the composite current collector copper foil is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material technology, and in particular to a composite film layer, a composite current collector, a preparation method, an electrode structure, a secondary battery and an electrical device. Background Art

[0002] In the prior art, composite current collector copper foil mainly adopts a sandwich structure of "metal-polymer material-metal", for example, a polymer material such as PET / PP is used as the middle layer, and copper metal layers are deposited on the upper and lower layers respectively.

[0003] PET is a polar material and has a strong bonding force with the metal layer. However, PET contains ester bonds and is easily corroded by organic electrolytes in lithium-ion batteries. After the lithium battery has been running for a period of time, the overall material structure of the composite current collector copper foil collapses, resulting in a decrease in the performance of the lithium battery. In addition, intermediate layer materials such as PET are easily degraded by the alcohol-based lithium components in the lithium battery. At the same time, because the copper layer obtained by magnetron sputtering is loose and porous, it cannot protect the substrate, which accelerates the rate at which the intermediate layer material is dissolved. PP is a non-polar material, which leads to its low adhesion. For this reason, the PP film needs to be corona treated to increase its surface tension, thereby improving its bonding strength with the metal layer. However, the improvement of corona treatment is limited. The surface tension of the PP film after corona treatment is unstable, and the surface tension will be greatly reduced after being stored for a period of time. The metal layer is thin, resulting in low mechanical strength of the overall composite current collector copper foil, which is not conducive to the subsequent coating processing of the composite current collector. Summary of the invention

[0004] Based on this, it is necessary to provide a composite film layer. The composite film layer of the present invention can improve the bonding strength between the polymer material and the metal layer, and improve the mechanical strength of the composite current collector copper foil.

[0005] An embodiment of the present application provides a composite film layer.

[0006] A composite membrane layer comprises an intermediate fabric layer and surface fabric layers respectively connected to at least one surface of the intermediate fabric layer, wherein the intermediate fabric layer is made of non-polar material, and the surface fabric layer is made of polar material or a combination of polar and non-polar materials.

[0007] In some of the embodiments, the composite film layer further includes a micro-melted intermediate connecting layer located between the surface fabric layer and the intermediate fabric layer and formed by laminating a portion of the surface fabric layer and a portion of the intermediate fabric layer.

[0008] In some of the embodiments, the non-polar material includes one or more of polypropylene, polyethylene, polystyrene, polytetrafluoroethylene, polyvinylidene chloride, polybutadiene, and polyisoprene.

[0009] In some embodiments, the polar material includes one or more of polyethylene terephthalate, polybutylene terephthalate, and polycarbonate.

[0010] In some of the embodiments, the non-polar material is a mixture of a low molecular weight non-polar material and a high molecular weight non-polar material, wherein the high molecular weight non-polar material has a weight average molecular weight greater than 200,000, and the low and high molecular weight non-polar materials have a weight average molecular weight between 50,000 and 150,000.

[0011] In some of the embodiments, in the surface fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 60wt%~80wt%, and the low molecular weight non-polar material in the non-polar material accounts for 20wt%-40wt%.

[0012] In some of the embodiments, in the intermediate fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 50wt%-70wt%, and the low molecular weight non-polar material in the non-polar material accounts for 30wt%-50wt%.

[0013] In some embodiments, the surface fabric layer is formed by weaving a first fiber bundle through a warp and weft crossing method, wherein the first fiber bundle includes a plurality of polar polymer material fiber bundle yarns and a plurality of non-polar polymer material fiber bundle yarns.

[0014] In some embodiments, in the first fiber bundle, the polar polymer material fiber bundle yarn prepared from the polar material accounts for 10wt%~30wt%, and the non-polar polymer material fiber bundle yarn prepared from the non-polar material accounts for 70wt%~90wt%.

[0015] In some embodiments, the diameter of the first fiber bundle is 1 μm-5 μm.

[0016] In some of the embodiments, the intermediate fabric layer is formed by weaving a second fiber bundle through a warp and weft crossing method, wherein the second fiber bundle includes a plurality of non-polar polymer material fiber bundle yarns.

[0017] In some embodiments, the diameter of the second fiber bundle is 1 μm-5 μm.

[0018] In some embodiments, the thickness of the surface fabric layer is less than the thickness of the middle fabric layer;

[0019] In some embodiments, the thickness of the surface fabric layer is 2 μm to 5 μm;

[0020] In some embodiments, the thickness of the intermediate fabric layer is 5 μm-10 μm.

[0021] In some embodiments, the porosity of the surface fabric layer is greater than the porosity of the middle fabric layer.

[0022] In some of the embodiments, the porosity of the surface fabric layer is 40% to 60%.

[0023] In some of the embodiments, the porosity of the middle fabric layer is 30%-50%.

[0024] In some of the embodiments, the pores of the surface fabric layer are partially aligned with the pores of the middle fabric layer.

[0025] In some of the embodiments, the alignment rate between the pores of the surface fabric layer and the pores of the middle fabric layer is 20% to 70%.

[0026] In some of the embodiments, the alignment rate between the pores of the surface fabric layer and the pores of the middle fabric layer is 30%-50%.

[0027] In some embodiments, the metal layer includes a copper layer;

[0028] In some embodiments, the thickness of the metal layer is 0.5 μm to 2 μm.

[0029] Another embodiment of the present application further provides a composite current collector.

[0030] A composite current collector comprises the composite film layer and a metal layer located on at least one surface of the composite film layer.

[0031] Another embodiment of the present application also provides a method for preparing a composite film layer.

[0032] A method for preparing a composite film layer comprises the following steps:

[0033] The intermediate fabric layer is woven with non-polar material, and the surface fabric layer connected to at least one surface of the intermediate fabric layer is woven with polar material or a combination of polar material and non-polar material. The intermediate fabric layer and the surface fabric layer on the surface form a composite membrane layer.

[0034] In some of the embodiments, the preparation method also includes the following steps: after weaving the intermediate fabric layer and the surface fabric layer on at least one surface thereof, laminating the intermediate fabric layer and the surface fabric layer on its surface, so that the low molecular weight non-polar material between the intermediate fabric layer and the surface fabric layer on its surface is micro-melted and fused to form a micro-melted intermediate connecting layer, wherein during the laminating treatment, the laminating temperature is between T-10°C and T+10°C, T is the melting temperature of the low molecular weight non-polar material, and the laminating pressure is 5GPa~20GPa.

[0035] Another embodiment of the present application also provides a method for preparing a composite current collector.

[0036] A method for preparing a composite current collector comprises the following steps:

[0037] Prepare a composite membrane layer by using the composite membrane layer or the method for preparing the composite membrane layer;

[0038] A metal layer is prepared on at least one surface of the composite film layer.

[0039] In some embodiments, the method for preparing the composite current collector further comprises the following steps:

[0040] A metal layer is prepared on at least one surface of the composite film layer by a deposition method, wherein during the deposition, a two-step process of magnetron sputtering and water electroplating is adopted, wherein in the magnetron sputtering process, the magnetron sputtering ion source power is 1kW~5kW, the target power is 5kW~20kW, and the magnetron layer thickness is 10nm~100nm;

[0041] After magnetron sputtering is completed, the metal layer is thickened by water electroplating process, with a current of 1A~10A, a line speed of 1m / min~10m / min, and the total thickness of the metal layer is controlled to be 0.5μm~2μm.

[0042] In some embodiments, the magnetron layer includes a bonding layer and a copper seed layer disposed on the bonding layer.

[0043] In some embodiments, the bonding layer is made of one or more materials selected from the group consisting of nickel, chromium, and nickel-chromium alloy.

[0044] Another embodiment of the present application further provides an electrode structure.

[0045] An electrode structure at least comprises the above-mentioned composite current collector, or the composite current collector prepared by the above-mentioned preparation method, wherein the electrode material in the electrode structure is coated or deposited on the surface of the composite current collector, and the composite current collector supports the electrode material and collects current.

[0046] Another embodiment of the present application provides a secondary battery.

[0047] A secondary battery at least comprises the above electrode structure.

[0048] Another embodiment of the present application further provides a battery module.

[0049] A battery module comprises the secondary battery mentioned above.

[0050] Another embodiment of the present application also provides a battery pack.

[0051] A battery pack comprises the secondary battery or the battery module mentioned above.

[0052] Another embodiment of the present application further provides an electrical device.

[0053] An electrical device at least comprises the above-mentioned secondary battery or the above-mentioned secondary battery or the above-mentioned battery module.

[0054] The composite film layer of the present invention can improve the bonding strength between the polymer material and the metal layer, and improve the mechanical strength of the composite current collector copper foil. Specifically, in the composite film layer of the present application, the composite film layer includes an intermediate fabric layer and a surface fabric layer respectively connected to at least one surface of the intermediate fabric layer. The intermediate fabric layer and the surface fabric layer can be prepared by a weaving method such as a warp and weft cross weaving method, which can make the composite film layer have good flexibility, improve the longitudinal and transverse tensile strength of the composite film layer, and ultimately improve the mechanical strength of the composite current collector. Furthermore, the intermediate fabric layer adopts a non-polar material, and the surface fabric layer adopts a polar material or a combination of a polar material and a non-polar material. The polar polymer material in the surface fabric layer can improve the bonding strength between the composite film layer and the metal layer, and ultimately improve the adhesion of the composite current collector.

[0055] In the composite membrane layer of the present invention, by setting the proportion of polar polymer fiber bundle yarn in the first fiber bundle of the surface fabric layer to 10wt%~30wt%, and the proportion of non-polar polymer fiber bundle yarn to 70wt%~90wt%, setting a relatively large proportion of non-polar polymer material can improve the corrosion resistance of the composite current collector at the application battery end to a certain extent. After the battery has been running for a period of time, the overall material structure of the composite current collector copper foil remains basically stable, the performance of the lithium battery is basically stable, the surface fabric layer is not easily degraded by the alcohol-based lithium component in the battery, and even if the metal layer is loose and porous and cannot protect the composite membrane layer, it will not accelerate the rate at which the composite membrane layer material is dissolved. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0057] In order to more completely understand the present application and its beneficial effects, the following description will be given in conjunction with the accompanying drawings. In the following description, the same reference numerals represent the same parts.

[0058] Figure 1 Schematic diagram of a composite membrane layer according to an embodiment of the present invention.

[0059] Description of Reference Numerals

[0060] 10. composite current collector copper foil; 100. composite film layer; 101. middle fabric layer; 102. surface fabric layer; 200. metal layer. DETAILED DESCRIPTION

[0061] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0062] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0063] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0064] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0065] In the description of the present invention, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0066] In this article, "optionally", "optional", "optional" means optional, that is, it means to be selected from any of the two parallel solutions of "yes" or "no". If there are multiple "optional" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent. In this application, the descriptions such as "optionally contain" and "optionally include" mean "contain or not contain".

[0067] In the present invention, unless otherwise stated, the sum of the parts of each component in the composition can be 100 parts by weight. Unless otherwise specified, the basis of the percentage (including weight percentage) of the present invention is the total weight of the composition, and "wt%" herein means mass percentage.

[0068] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for a broad range of quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0069] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0070] The embodiment of the present application provides a composite film layer to solve at least one of the following technical problems existing in the composite current collector copper foil in the prior art: (1) PET film is easily corroded by the organic electrolyte in the lithium ion battery. After the lithium battery has been running for a period of time, the overall material structure of the composite current collector copper foil collapses, resulting in a decrease in the performance of the lithium battery; (2) PET and other intermediate layer materials are easily degraded by the alcohol-based lithium component in the lithium battery. The copper layer is loose and porous and cannot protect the substrate, which accelerates the rate at which the intermediate layer material is dissolved; (3) PP film has poor adhesion to the metal layer; (4) The metal layer is thin, resulting in low overall mechanical strength of the composite current collector copper foil, which is not conducive to the subsequent coating processing of the composite current collector. The composite film layer will be described below in conjunction with the accompanying drawings.

[0071] The composite film layer provided in the embodiments of the present application is exemplary, see Figure 1 As shown, Figure 1 A schematic diagram of the structure of the composite membrane layer provided in an embodiment of the present application.

[0072] Exemplarily, a composite membrane layer comprises an intermediate fabric layer and a surface fabric layer connected to at least one surface of the intermediate fabric layer. The intermediate fabric layer is made of non-polar material. The surface fabric layer is made of polar material or a combination of polar material and non-polar material.

[0073] In some embodiments, both surfaces of the middle fabric layer have surface fabric layers respectively.

[0074] In some embodiments, the composite film layer also includes a micro-melting intermediate connecting layer located between the surface fabric layer and the intermediate fabric layer and formed by laminating a portion of the surface fabric layer and a portion of the intermediate fabric layer. It should be noted that the micro-melting intermediate connecting layer in the present application can be obtained by laminating the intermediate fabric layer and the surface fabric layer on its surface, so that the low molecular weight non-polar material between the intermediate fabric layer and the surface fabric layer on its surface is micro-melted and fused to form a micro-melting intermediate connecting layer, wherein during the laminating process, the laminating temperature is between T-10°C and T+10°C, T is the melting temperature of the low molecular weight non-polar material, and the laminating pressure is 5GPa~20GPa.

[0075] In some of the embodiments, the surface fabric layer adopts a combination of polar material and non-polar material. In the present application, the surface fabric layer adopts a polar material or a combination of polar material and non-polar material. The polar material can improve the bonding strength between the substrate used for the composite current collector and copper or aluminum, and the addition of non-polar material can improve the corrosion resistance of the composite current collector at the battery end to a certain extent. The melting temperature of the polar material needs to be greater than the melting temperature of the non-polar material to avoid melting of the polar material during pressing. Although some polar materials are not resistant to organic electrolytes in lithium-ion batteries, the non-polar material part is sufficient to support the composite current collector composite film layer structure, and will not cause the overall material structure of the composite copper foil to collapse after a period of operation in the lithium battery.

[0076] In some of the embodiments, the non-polar material includes one or more of polypropylene, polyethylene, polystyrene, polytetrafluoroethylene, polyvinylidene chloride, polybutadiene, and polyisoprene.

[0077] In some embodiments, the polar material includes one or more of polyethylene terephthalate, polybutylene terephthalate, and polycarbonate.

[0078] In some embodiments, the non-polar material is a mixture of a low molecular weight non-polar material and a high molecular weight non-polar material, wherein the weight average molecular weight of the high molecular weight non-polar material is greater than 200,000, and the weight average molecular weight of the low molecular weight non-polar material is between 50,000 and 150,000. The use of low molecular weight and high molecular weight non-polar materials in combination can combine the advantages of both, thereby improving the overall performance of the material. The advantages include (1) improving processing performance: low molecular weight components usually have lower viscosity, which helps to improve fluidity during processing (such as injection molding, extrusion, etc.), making molding easier and able to fill complex mold structures. High molecular weight components ensure the mechanical strength and toughness of the final product, and even during processing, the quality of the finished product will not be affected by molecular chain breakage. (2) enhancing physical and mechanical properties: the high molecular weight part provides better tensile strength, impact strength and wear resistance, ensuring the durability and reliability of the material in application. The low molecular weight component can increase the flexibility and elasticity of the material to a certain extent, especially under low temperature conditions, reducing the possibility of brittle cracking. (3) Optimizing thermal stability: High molecular weight polymers generally have better heat resistance and can maintain their shape and performance at higher temperatures, so that the composite film layer will not undergo significant deformation during micro-melting heating; (4) After the low molecular weight non-polar material is micro-melted, the pore size in the surface fabric layer is reduced, avoiding the pore size formed by weaving in the surface fabric layer from being too large, and preventing excessive deposition of magnetron metal on the inner wall of the pores, thereby affecting the thickness of the magnetron metal layer on the surface of the composite film layer.

[0079] In some embodiments, the low molecular weight non-polar material includes one or more of polypropylene, polyethylene, polystyrene, polytetrafluoroethylene, polyvinylidene chloride, polybutadiene, and polyisoprene.

[0080] In some of the embodiments, the high molecular weight non-polar material includes one or more of polypropylene, polyethylene, polystyrene, polytetrafluoroethylene, polyvinylidene chloride, polybutadiene, and polyisoprene.

[0081] In some of the embodiments, in the surface fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 60wt%~80wt%, and the low molecular weight non-polar material in the non-polar material accounts for 20wt%-40wt%.

[0082] In some of the embodiments, in the intermediate fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 50wt%-70wt%, and the low molecular weight non-polar material in the non-polar material accounts for 30wt%-50wt%.

[0083] In some embodiments, the surface fabric layer is formed by weaving a first fiber bundle through a warp and weft crossing method, wherein the first fiber bundle includes a plurality of polar polymer material fiber bundle yarns and a plurality of non-polar polymer material fiber bundle yarns.

[0084] In some embodiments, in the first fiber bundle, the proportion of the polar polymer fiber bundle yarn prepared from the polar material is 10wt%~30wt%, and the proportion of the non-polar polymer fiber bundle yarn prepared from the non-polar material is 70wt%~90wt%. In the composite film layer of the present invention, by setting the composite film layer, in the first fiber bundle of the surface fabric layer, the proportion of the polar polymer fiber bundle yarn is 10wt%~30wt%, and the proportion of the non-polar polymer fiber bundle yarn is 70wt%~90wt%, the non-polar polymer material with a relatively large proportion can improve the corrosion resistance of the composite current collector at the end of the application battery to a certain extent, after the battery has been running for a period of time, the overall material structure of the composite current collector copper foil remains basically stable, the performance of the lithium battery is basically stable, the surface fabric layer is not easily degraded by the alcohol group lithium component in the battery, even if the metal layer is loose and porous and cannot protect the composite film layer, it will not accelerate the rate of dissolution of the composite film layer material.

[0085] In some embodiments, the diameter of the first fiber bundle is 1 μm to 5 μm. The diameter of the first fiber bundle includes but is not limited to: 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or a range between any two of the foregoing.

[0086] In some of the embodiments, the intermediate fabric layer is formed by weaving a second fiber bundle through a warp and weft crossing method, wherein the second fiber bundle includes a plurality of non-polar polymer material fiber bundle yarns.

[0087] In some embodiments, the diameter of the second fiber bundle is 1 μm to 5 μm. The diameter of the second fiber bundle includes but is not limited to: 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or a range between any two of the foregoing.

[0088] In some embodiments, the thickness of the surface fabric layer is smaller than the thickness of the middle fabric layer.

[0089] In some embodiments, the thickness of the surface fabric layer is 2 μm to 5 μm. The thickness of the surface fabric layer includes but is not limited to: 2 μm, 3 μm, 4 μm, 5 μm or a range between any two of the foregoing.

[0090] In some embodiments, the thickness of the intermediate fabric layer is 5 μm-10 μm. The thickness of the intermediate fabric layer includes but is not limited to: 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range between any two of the foregoing.

[0091] In some embodiments, the porosity of the surface fabric layer is greater than the porosity of the middle fabric layer.

[0092] In some embodiments, the porosity of the surface fabric layer is 40% to 60%. The porosity of the surface fabric layer includes but is not limited to: 40%, 45%, 50%, 55%, 60% or a range between any two of the foregoing.

[0093] In some embodiments, the porosity of the middle fabric layer is 30% to 50%. The porosity of the middle fabric layer includes but is not limited to: 30%, 35%, 40%, 45%, 50% or a range between any two of the foregoing.

[0094] In some of the embodiments, the pores of the surface fabric layer are partially aligned with the pores of the middle fabric layer.

[0095] In some embodiments, the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is 20% to 70%. The values ​​of the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer include but are not limited to: 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or a range between any two of the foregoing. It should be noted that the alignment rate herein is the ratio between the number of pores that penetrate the pores of the surface fabric layer and the pores of the middle fabric layer and the number of pores of the surface fabric layer as a whole.

[0096] In some embodiments, the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is 30% to 50%. The values ​​of the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer include but are not limited to: 30%, 35%, 40%, 45%, 50% or a range between any two of the foregoing. In the present application, the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is 30% to 50%, which can achieve the following technical effects: (1) Thermal management: 30% to 50% pore alignment helps to improve the heat conduction inside the current collector, so that the heat can be more evenly distributed or more easily dissipated, which is beneficial to the thermal management of the battery. (2) 30% to 50% pore alignment ensures that suitable magnetron metal materials are deposited in the pores, ensures that the composite film layer and the metal layer have high adhesion, and improves the corrosion resistance of the composite current collector.

[0097] In some embodiments, the metal layer includes a copper layer.

[0098] In some embodiments, the thickness of the metal layer is 0.5 μm to 2 μm. Preferably, the thickness of the metal layer is 1 μm to 1.5 μm. The thickness of the metal layer includes but is not limited to: 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm or a range between any two of the foregoing.

[0099] Another embodiment of the present application further provides a composite current collector.

[0100] A composite current collector comprises a composite film layer and a metal layer located on at least one surface of the composite film layer; wherein the composite film layer comprises an intermediate fabric layer and a surface fabric layer respectively connected to at least one surface of the intermediate fabric layer, the intermediate fabric layer adopts a non-polar material, and the surface fabric layer adopts a polar material or a combination of a polar material and a non-polar material.

[0101] Another embodiment of the present application also provides a method for preparing a composite film layer.

[0102] It should be noted that, in this article, unless otherwise specified, each reaction step can be carried out in the order described herein, or can be carried out in a non-sequential manner. For example, other steps may be included between each reaction step, and the order of the reaction steps may also be appropriately swapped. This can be determined by the technician based on conventional knowledge and experience. Preferably, the reaction method herein is carried out sequentially.

[0103] A method for preparing a composite film layer comprises the following steps:

[0104] The intermediate fabric layer is woven with non-polar material, and the surface fabric layer connected to at least one surface of the intermediate fabric layer is woven with polar material or a combination of polar material and non-polar material. The intermediate fabric layer and the surface fabric layer on the surface form a composite membrane layer.

[0105] In some of the embodiments, the method for preparing the composite membrane layer also includes the following steps: after weaving the intermediate fabric layer and the surface fabric layer on its surface, laminating the intermediate fabric layer and the surface fabric layer on its surface so that the low molecular weight non-polar material between the intermediate fabric layer and the surface fabric layer on its surface is micro-melted and fused to form a micro-melted intermediate connecting layer, wherein during the laminating treatment, the laminating temperature is between T-10°C and T+10°C, T is the melting temperature of the low molecular weight non-polar material, and the laminating pressure is 5GPa~20GPa.

[0106] Another embodiment of the present application also provides a method for preparing a composite current collector.

[0107] A method for preparing a composite current collector comprises the following steps:

[0108] The composite membrane layer is prepared by adopting the composite membrane layer preparation method.

[0109] A metal layer is prepared on at least one surface of the composite film layer.

[0110] In some embodiments, the method for preparing the composite current collector further comprises the following steps:

[0111] A metal layer is prepared on at least one surface of the composite film layer by a deposition method. When preparing the metal layer, a two-step process of magnetron sputtering and water electroplating is adopted, wherein in the magnetron sputtering process, the magnetron sputtering ion source power is 1kW~5kW, the target power is 5kW~20kW, and the magnetron layer thickness is 10nm~100nm;

[0112] After magnetron sputtering is completed, the metal layer is thickened by water electroplating process, with a current of 1A~10A, a line speed of 1m / min~10m / min, and the total thickness of the metal layer is controlled to be 0.5μm~2μm.

[0113] In some embodiments, the magnetron layer includes a bonding layer and a copper seed layer disposed on the bonding layer.

[0114] In some embodiments, the bonding layer is made of one or more materials selected from the group consisting of nickel, chromium, and nickel-chromium alloy.

[0115] Another embodiment of the present application further provides an electrode structure.

[0116] An electrode structure at least comprises the above-mentioned composite current collector, or the composite current collector prepared by the above-mentioned preparation method, wherein the electrode material in the electrode structure is coated or deposited on the surface of the composite current collector, and the composite current collector supports the electrode material and collects current.

[0117] Another embodiment of the present application provides a secondary battery.

[0118] A secondary battery at least comprises the above electrode structure.

[0119] Another embodiment of the present application further provides a battery module.

[0120] A battery module comprises the secondary battery mentioned above.

[0121] Another embodiment of the present application also provides a battery pack.

[0122] A battery pack comprises the secondary battery or the battery module mentioned above.

[0123] Another embodiment of the present application further provides an electrical device.

[0124] An electrical device at least comprises the above-mentioned secondary battery or the above-mentioned secondary battery or the above-mentioned battery module.

[0125] Example 1

[0126] This embodiment provides a composite current collector.

[0127] The composite current collector includes a composite film layer and metal layers located on both surfaces of the composite film layer. The composite film layer includes an intermediate fabric layer and surface fabric layers respectively connected to both surfaces of the intermediate fabric layer, the intermediate fabric layer is made of non-polar material, and the surface fabric layer is made of polar material or a combination of polar material and non-polar material.

[0128] The non-polar material includes PP (polypropylene). The polar material includes PET (polyethylene terephthalate). The non-polar material is a mixture of a low molecular weight non-polar material and a high molecular weight non-polar material, wherein the high molecular weight non-polar material is PP with a molecular weight of 250,000, and the low molecular weight non-polar material is PP with a molecular weight of 50,000.

[0129] In the surface fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 60wt%, and the low molecular weight non-polar material in the non-polar material accounts for 40wt%. In the middle fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 70wt%, and the low molecular weight non-polar material in the non-polar material accounts for 30wt%.

[0130] The surface fabric layer is formed by weaving a first fiber bundle through a warp and weft crossing method, wherein the first fiber bundle includes a plurality of polar polymer fiber bundle yarns and a plurality of non-polar polymer fiber bundle yarns. In the first fiber bundle, the polar polymer fiber bundle yarn accounts for 10wt%, and the non-polar polymer fiber bundle yarn accounts for 90wt%. The diameter of the first fiber bundle is 1μm. The polar polymer fiber bundle yarn is made of PET material. The non-polar polymer fiber bundle yarn is made of PET material.

[0131] The middle fabric layer is formed by weaving a second fiber bundle through a warp and weft crossing method, wherein the second fiber bundle comprises a plurality of non-polar polymer fiber bundle yarns and the diameter of the second fiber bundle is 1 μm.

[0132] The thickness of the surface fabric layer is less than that of the middle fabric layer. The thickness of the surface fabric layer is 2 μm. The thickness of the middle fabric layer is 5 μm.

[0133] The porosity of the surface fabric layer is greater than that of the middle fabric layer, the porosity of the surface fabric layer is 40%, and the porosity of the middle fabric layer is 30%.

[0134] The pores of the surface fabric layer are partially aligned with the pores of the middle fabric layer. The alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is 70%.

[0135] The metal layer includes a copper layer and has a thickness of 1 μm.

[0136] Based on the above parameter control, the composite current collector of this embodiment is prepared by the following method.

[0137] (1) A middle fabric layer is woven with non-polar material, and a surface fabric layer connected to two surfaces of the middle fabric layer is woven with polar material or a combination of polar material and non-polar material. The middle fabric layer and the surface fabric layers on the two surfaces form a composite membrane layer.

[0138] (2) After weaving the intermediate fabric layer and the surface fabric layers on its two surfaces, the intermediate fabric layer and the surface fabric layers on its two surfaces are pressed together so that the low molecular weight non-polar material between the intermediate fabric layer and the surface fabric layers on its two surfaces is micro-melted and fused to form a micro-melted intermediate connecting layer, wherein during the pressing process, the pressing temperature is 150° C., T is the melting temperature of the low molecular weight non-polar material, and the pressing pressure is 5 GPa.

[0139] (3) A metal layer is prepared on both surfaces of the composite film layer by a deposition method. A two-step process of magnetron sputtering and water electroplating is adopted, wherein in the magnetron sputtering process, the magnetron sputtering ion source power is 3kW, the target power is 10kW, and the magnetron layer thickness is 50nm; after the magnetron sputtering is completed, the metal layer is thickened by a water electroplating process, the current is 5A, the line speed is 5m / min, and the total thickness of the metal layer is controlled to be 1μm. The magnetron layer includes a bonding layer and a copper seed layer disposed on the bonding layer. The bonding layer is prepared by a material including nickel.

[0140] Example 2

[0141] This embodiment provides a composite current collector.

[0142] The composite current collector of this embodiment is basically the same as that of Embodiment 1, except that, in this embodiment, in the surface fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 80wt%, and the low molecular weight non-polar material in the non-polar material accounts for 20wt%.

[0143] Example 3

[0144] This embodiment provides a composite current collector.

[0145] The composite current collector of this embodiment is basically the same as that of Embodiment 1, except that, in this embodiment, in the intermediate fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 50wt%, and the low molecular weight non-polar material in the non-polar material accounts for 50wt%.

[0146] Example 4

[0147] This embodiment provides a composite current collector.

[0148] The composite current collector of this embodiment is basically the same as that of Embodiment 1, except that, in this embodiment, in the first fiber bundle, the polar polymer fiber bundle yarn accounts for 30wt%, and the non-polar polymer fiber bundle yarn accounts for 70wt%.

[0149] Example 5

[0150] This embodiment provides a composite current collector.

[0151] The composite current collector of this embodiment is substantially the same as that of embodiment 1, except that, in this embodiment, the diameter of the first fiber bundle is 5 μm, and the diameter of the second fiber bundle is 5 μm.

[0152] Example 6

[0153] This embodiment provides a composite current collector.

[0154] The composite current collector of this embodiment is substantially the same as that of Embodiment 1, except that, in this embodiment, the porosity of the surface fabric layer is 60%, and the porosity of the middle fabric layer is 50%.

[0155] Example 7

[0156] This embodiment provides a composite current collector.

[0157] The composite current collector of this embodiment is substantially the same as that of embodiment 1, except that, in this embodiment, the pores of the surface fabric layer are partially aligned with the pores of the middle fabric layer, and the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is 30%.

[0158] Comparative Example 1

[0159] This comparative example provides a composite current collector.

[0160] The composite current collector of this comparative example is basically the same as that of Example 1, except that in this comparative example, in the surface fabric, the high molecular weight non-polar material in the non-polar material accounts for 90wt%, and the low molecular weight non-polar material in the non-polar material accounts for 10wt%. That is, in the surface fabric, the low molecular weight non-polar material in the non-polar material accounts for too little. In this comparative example, the surface fabric and the middle fabric are difficult to bond together, and the surface and middle fabrics are easily delaminated under tension, resulting in reduced strength of the composite current collector.

[0161] Comparative Example 2

[0162] This comparative example provides a composite current collector.

[0163] The composite current collector of this comparative example is basically the same as that of Example 1, except that in this comparative example, in the surface fabric, the high molecular weight non-polar material in the non-polar material accounts for 50wt%, and the low molecular weight non-polar material in the non-polar material accounts for 50wt%. That is, in the surface fabric, the low molecular weight non-polar material in the non-polar material accounts for too much. In this comparative example, the overall strength of the composite film fabric is low, resulting in a decrease in the strength of the composite current collector.

[0164] Comparative Example 3

[0165] This comparative example provides a composite current collector.

[0166] The composite current collector of this comparative example is basically the same as that of Example 1, except that in this comparative example, in the intermediate fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 80wt%, and the low molecular weight non-polar material in the non-polar material accounts for 20wt%. That is, in the intermediate fabric layer, the low molecular weight non-polar material in the non-polar material accounts for too little. In this comparative example, it will make it difficult to bond the surface fabric and the intermediate fabric together, and it is easy to cause the surface fabric and the intermediate fabric to be delaminated under tension, resulting in a reduction in the strength of the composite current collector.

[0167] Comparative Example 4

[0168] This comparative example provides a composite current collector.

[0169] The composite current collector of this comparative example is basically the same as that of Example 1, except that in this comparative example, in the intermediate fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 40wt%, and the low molecular weight non-polar material in the non-polar material accounts for 60wt%. That is, in the intermediate fabric layer, the low molecular weight non-polar material in the non-polar material accounts for too much. In this comparative example, the overall strength of the composite film layer fabric is low, resulting in a decrease in the strength of the composite current collector.

[0170] Comparative Example 5

[0171] This comparative example provides a composite current collector.

[0172] The composite current collector of this comparative example is basically the same as that of Example 1, except that, in this comparative example, in the first fiber bundle, the proportion of the polar polymer fiber bundle yarn is 5wt%, and the proportion of the non-polar polymer fiber bundle yarn is 95wt%. That is, in this comparative example, in the first fiber bundle, the proportion of the polar polymer fiber bundle yarn is too small. In this comparative example, the specific surface area of ​​the metal layer in contact with the polar material is small, resulting in reduced adhesion of the finished composite current collector. The reduced adhesion makes it easy for the electrolyte to invade the composite film layer, resulting in poor corrosion resistance, which makes the composite current collector easy to corrode.

[0173] Comparative Example 6

[0174] This comparative example provides a composite current collector.

[0175] The composite current collector of this comparative example is basically the same as that of Example 1, except that, in this comparative example, the proportion of the polar polymer fiber bundle yarn in the first fiber bundle is 40wt%, and the proportion of the non-polar polymer fiber bundle yarn is 60wt%. That is, in this comparative example, the proportion of the polar polymer fiber bundle yarn in the first fiber bundle is too high. In this comparative example, the excessive content of polyester materials is easily corroded by the electrolyte in the battery, resulting in easy corrosion of the composite current collector.

[0176] Comparative Example 7

[0177] This comparative example provides a composite current collector.

[0178] The composite current collector of this comparative example is basically the same as that of Example 1, except that, in this comparative example, the thickness of the surface fabric layer is 10 μm. In some of the embodiments, the thickness of the intermediate fabric layer is 5 μm. That is, in this comparative example, the thickness of the surface fabric layer is greater than the thickness of the intermediate fabric layer. In this comparative example, the surface fabric layer is relatively thick, resulting in an increase in the pore depth. During the sputtering process, the metal cannot be deposited into the pores of the intermediate fabric layer, and the specific surface area of ​​the metal layer in contact with the composite film layer is reduced, resulting in a decrease in the adhesion of the finished composite current collector. In addition, the reduced adhesion of the finished composite current collector causes the electrolyte to invade the composite film layer, resulting in poor corrosion resistance, which causes the composite current collector to corrode easily.

[0179] Comparative Example 8

[0180] This comparative example provides a composite current collector.

[0181] The composite current collector of this comparative example is basically the same as that of Example 1, except that, in this comparative example, the porosity of the surface fabric layer is 40%. The porosity of the middle fabric layer is 60%. That is, in this comparative example, the porosity of the surface fabric layer is less than the porosity of the middle fabric layer. In this comparative example, the porosity of the surface fabric layer is low, and the metal cannot be deposited into the pores of the middle fabric layer during the sputtering process, and the specific surface area of ​​the metal layer in contact with the composite film layer is reduced, resulting in a decrease in the adhesion of the finished composite current collector. In addition, the decrease in the adhesion of the finished composite current collector causes the electrolyte to invade the composite film layer, resulting in poor corrosion resistance, which makes the composite current collector easy to corrode.

[0182] Comparative Example 9

[0183] This comparative example provides a composite current collector.

[0184] The composite current collector of this comparative example is basically the same as that of Example 1, except that, in this comparative example, the pores of the surface fabric layer are partially aligned with the pores of the middle fabric layer, and the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is 80%. That is, in this comparative example, the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is too large. In this comparative example, a large amount of metal is deposited into the pores of the middle fabric layer during the sputtering process, resulting in a too small thickness of the sputtered metal layer deposited on the surface of the composite film layer, a decrease in the adhesion of the finished composite current collector, and a decrease in the adhesion of the finished composite current collector, resulting in the electrolyte invading the composite film layer, resulting in poor corrosion resistance, and causing the composite current collector to corrode easily.

[0185] Comparative Example 10

[0186] This comparative example provides a composite current collector.

[0187] The composite current collector of this comparative example is basically the same as that of Example 1, except that, in this comparative example, the pores of the surface fabric layer are partially aligned with the pores of the middle fabric layer, and the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is 10%. That is, in this comparative example, the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is too small. In this comparative example, it is difficult to sputter the metal seed layer into the middle fabric layer by the sputtering process, the specific surface area of ​​the metal layer in contact with the surface fabric layer is reduced, the adhesion of the finished composite current collector is reduced, and the reduced adhesion of the finished composite current collector causes the electrolyte to invade the composite film layer, resulting in poor corrosion resistance, which makes the composite current collector easy to corrode.

[0188] The performance tests were performed on the composite current collectors in Examples 1 to 8 and Comparative Examples 1 to 10, respectively.

[0189] Test method:

[0190] Tensile strength test: Use a universal tensile machine for testing, with a composite current collector sample width of 15 mm, a clamp distance of 50 mm, and a test speed of 200 m / min. The tensile strength is the strength when the metal layer and the braided layer of the composite current collector are broken at the same time.

[0191] Adhesion test: 100-grid method test, use a 100-grid knife to evenly cut squares of a certain size on the surface of the composite current collector sample, stick the test tape 3M681 in the 100 grids, quickly pull up the 3M tape, and count the proportion of the number of squares where the metal layer of the composite current collector is stuck to the tape and separated from the composite film layer to the total number of squares.

[0192] Corrosion resistance test: the solution is lithium battery electrolyte, the test temperature is 85°C, the immersion time is 72h, the composite current collector size is 3cm×3cm, and the proportion of the area of ​​the metal layer of the composite current collector that has fallen off to the overall area is observed.

[0193] The test results are shown in Table 1.

[0194] Table 1

[0195]

[0196] In summary, the composite film layer of the present invention can improve the bonding strength between the polymer material and the metal layer, and improve the mechanical strength of the composite current collector copper foil. Specifically, in the composite film layer of the present application, the composite film layer includes an intermediate fabric layer and a surface fabric layer respectively connected to the two surfaces of the intermediate fabric layer. The intermediate fabric layer and the surface fabric layer can be prepared by a weaving method such as warp and weft cross weaving, which can make the composite film layer have good flexibility, improve the longitudinal and transverse tensile strength of the composite film layer, and ultimately improve the mechanical strength of the composite current collector. Furthermore, the intermediate fabric layer adopts non-polar materials, and the surface fabric layer adopts polar materials or a combination of polar materials and non-polar materials. The polar polymer material in the surface fabric layer can improve the bonding strength between the composite film layer and the metal layer, and ultimately improve the adhesion of the composite current collector.

[0197] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0198] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0199] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A composite film layer, characterized in that: The composite membrane layer comprises an intermediate fabric layer and a surface fabric layer respectively connected to at least one surface of the intermediate fabric layer. The intermediate fabric layer adopts a non-polar material, and the surface fabric layer adopts a polar material or a combination of a polar material and a non-polar material.

2. The composite film layer according to claim 1, characterized in that: The composite film layer also includes a micro-melting intermediate connection layer located between the surface fabric layer and the intermediate fabric layer and formed by laminating a portion of the surface fabric layer and a portion of the intermediate fabric layer; and / or, the non-polar material comprises one or more of polypropylene, polyethylene, polystyrene, polytetrafluoroethylene, polyvinylidene chloride, polybutadiene, and polyisoprene; And / or, the polar material includes a polyester material, and the polyester material includes one or more of polyethylene terephthalate, polybutylene terephthalate, and polycarbonate.

3. The composite film layer according to claim 1, characterized in that: The non-polar material is a mixture of a low molecular weight non-polar material and a high molecular weight non-polar material, wherein the high molecular weight non-polar material has a weight average molecular weight greater than 200,000, and the low and high molecular weight non-polar materials have a weight average molecular weight between 50,000 and 150,000.

4. The composite film layer according to claim 3, characterized in that: In the surface fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 60wt% to 80wt%, and the low molecular weight non-polar material in the non-polar material accounts for 20wt% to 40wt%; And / or, in the intermediate fabric layer, the high molecular weight non-polar material in the non-polar material accounts for 50wt%-70wt%, and the low molecular weight non-polar material in the non-polar material accounts for 30wt%-50wt%.

5. The composite film layer according to any one of claims 1 to 4, characterized in that: The surface fabric layer is formed by weaving a first fiber bundle through a warp and weft crossing method, wherein the first fiber bundle includes a plurality of polar polymer material fiber bundle yarns and a plurality of non-polar polymer material fiber bundle yarns.

6. The composite film layer according to claim 5, characterized in that: In the first fiber bundle, the polar polymer fiber bundle yarn made of the polar material accounts for 10wt% to 30wt%, and the non-polar polymer fiber bundle yarn made of the non-polar material accounts for 70wt% to 90wt%; And / or, the diameter of the first fiber bundle is 1 μm~5 μm.

7. The composite film layer according to any one of claims 1 to 4 and 6, characterized in that: The intermediate fabric layer is formed by weaving a second fiber bundle through a warp and weft crossing method, wherein the second fiber bundle comprises a plurality of non-polar polymer fiber bundle yarns; and / or, the thickness of the surface fabric layer is less than the thickness of the middle fabric layer; And / or, the thickness of the surface fabric layer is 2 μm to 5 μm; and / or, the thickness of the intermediate fabric layer is 5 μm-10 μm; and / or, the porosity of the surface fabric layer is greater than the porosity of the middle fabric layer; And / or, the porosity of the surface fabric layer is 40% to 60%; And / or, the porosity of the middle fabric layer is 30% to 50%; and / or, the pores of the surface fabric layer are partially aligned with the pores of the middle fabric layer; And / or, the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is 20%-70%, preferably, the alignment rate of the pores of the surface fabric layer and the pores of the middle fabric layer is 30%-50%.

8. A composite current collector, characterized in that: It comprises the composite film layer according to any one of claims 1 to 7 and a metal layer located on at least one surface of the composite film layer.

9. The composite current collector according to claim 8, characterized in that: The metal layer includes a copper layer; And / or, the thickness of the metal layer is 0.5 μm to 2 μm, preferably, the thickness of the metal layer is 1 μm to 1.5 μm.

10. A method for preparing a composite film layer, characterized in that: The steps include: An intermediate fabric layer is woven with non-polar material, and a surface fabric layer connected to at least one surface of the intermediate fabric layer is woven with polar material or a combination of polar material and non-polar material. The intermediate fabric layer and the surface fabric layer on its surface form a composite membrane layer.

11. The method for preparing a composite film layer according to claim 10, characterized in that: It also includes the following steps: after weaving the intermediate fabric layer and the surface fabric layer on at least one surface thereof, laminating the intermediate fabric layer and the surface fabric layer on its surface, so that the low molecular weight non-polar material between the intermediate fabric layer and the surface fabric layer on its surface is micro-melted and fused to form a micro-melted intermediate connecting layer, wherein during the laminating process, the laminating temperature is between T-10°C and T+10°C, T is the melting temperature of the low molecular weight non-polar material, and the laminating pressure is 5GPa~20GPa.

12. A method for preparing a composite current collector, characterized in that: The steps include: A composite membrane layer according to any one of claims 1 to 7, or a composite membrane layer prepared by the method for preparing a composite membrane layer according to claim 10 or 11; A metal layer is prepared on the surface of the composite film layer.

13. An electrode structure, characterized in that: At least comprising the composite current collector according to claim 8 or 9, or the composite current collector prepared by the preparation method according to claim 12, wherein the electrode material in the electrode structure is coated or deposited on the surface of the composite current collector, and the composite current collector supports the electrode material and collects current.

14. A secondary battery, characterized in that: At least comprising the electrode structure described in claim 13.

15. An electrical device, characterized in that: At least comprising the electrode structure according to claim 13, or at least comprising the secondary battery according to claim 14.